Sex dependent effects of silver nanoparticles on the zebrafish gut microbiota. Issue 3 (29th January 2018) - Ma, Yanbo; Song, Liyan; Lei, Yu; Jia, Panpan; Lu, Chunjiao; Wu, Jianfeng; Xi, Chuanwu; Strauss, Phyllis R.; Pei, De-Sheng
Abstract : Silver nanoparticles (AgNPs), the most prevalent commercial nanomaterial products, are widely released into the environment. Abstract : Silver nanoparticles (AgNPs), the most prevalent commercial nanomaterial products, are widely released into the environment. AgNPs are toxic to various aquatic organisms, but their influence on the aquatic organism's gut microbiota remains unknown. Here, we characterized the bacterial communities in the guts of adult zebrafish treated with AgNPs (10, 33 or 100 μg L −1 ) for 35 days and also measured the concentration of AgNPs in the zebrafish digestive tract. As expected, dose dependence of AgNP accumulation was observed in the digestive tract, accompanied by decreased overall microbial richness and diversity. To our surprise, however, the effects of the AgNP treatment on the gut microbiota of male and female fish were not the same; furthermore, AgNPs significantly altered the relative composition of the bacterial species in the community harbored in male zebrafish but not in females. This research investigates and compares zebrafish intestinal microbiota after AgNP exposure, pointing to the potential health risk to aquatic organisms from alteration of gut microbiota.